2006
DOI: 10.1063/1.2150248
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed plasma polymerized dichlorotetramethyldisiloxane high-k gate dielectrics for polymer field-effect transistors

Abstract: Polymerized dichlorotetramethyldisiloxane (DCTMDS) films deposited by radio-frequency pulsed plasma polymerization (PPP) demonstrated very high dielectric constants for a polymer-based system, in the range of 7–10. The high dielectric constants of PPP DCTMDS films are due to the high polarizability of the DCTMDS monomer. The pulsed plasma duty cycle (on/off) resulted in slightly higher dielectric constant DCTMDS films for higher duty cycles. The variation of dielectric constants does not show any trend with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The highly adherent pinhole-free deposits may be readily formed on surfaces from plasmas struck in a range of volatile organic compounds to achieve many different types of chemistry. , For most organic compounds with a significant vapor pressure under vacuum, it is possible to strike a discharge in the pure monomer, and for low-input powers (a few Watts), the monomer functionality can be retained in the deposit . Through important but empirical research, it has been shown that in low-power continuous-wave (CW) radio-frequency (RF) plasmas, reduced monomer fragmentation in the discharge leads to high functional group retention in the films. In a refinement of the technique, it has been found that for a host of different monomers good control over the surface chemistry can be achieved by pulsing the RF power, with long off periods t off (milliseconds) and short on periods t on (in the hundreds of microseconds range). The short duration of the on period is sufficient to produce radicals and charged species in the plasma necessary for the polymerization to proceed (primarily in the off period).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly adherent pinhole-free deposits may be readily formed on surfaces from plasmas struck in a range of volatile organic compounds to achieve many different types of chemistry. , For most organic compounds with a significant vapor pressure under vacuum, it is possible to strike a discharge in the pure monomer, and for low-input powers (a few Watts), the monomer functionality can be retained in the deposit . Through important but empirical research, it has been shown that in low-power continuous-wave (CW) radio-frequency (RF) plasmas, reduced monomer fragmentation in the discharge leads to high functional group retention in the films. In a refinement of the technique, it has been found that for a host of different monomers good control over the surface chemistry can be achieved by pulsing the RF power, with long off periods t off (milliseconds) and short on periods t on (in the hundreds of microseconds range). The short duration of the on period is sufficient to produce radicals and charged species in the plasma necessary for the polymerization to proceed (primarily in the off period).…”
Section: Introductionmentioning
confidence: 99%
“…6 Through important but empirical research, it has been shown that in low-power continuous-wave (CW) radio-frequency (RF) plasmas, reduced monomer fragmentation in the discharge leads to high functional group retention in the films. [6][7][8][9][10] In a refinement of the technique, it has been found that for a host of different monomers good control over the surface chemistry can be achieved by pulsing the RF power, [11][12][13][14][15][16][17][18][19] with long off periods t off (milliseconds) and short on periods t on (in the hundreds of microseconds range). The short duration of the on period is sufficient to produce radicals and charged species in the plasma necessary for the polymerization to proceed (primarily in the off period).…”
Section: Introductionmentioning
confidence: 99%